Trajectory prediction of moored vessels with reduced station keeping capability due to exceeded anchor load limits - Josten, Michal (Volume 1: Offshore Technology; Offshore Geotechnics, 2019)
This paper presents the development and application of an in-house manoeuvring method for the prediction of the track of a moored vessel in the case of a temporary or total loss of station keeping capability as a result of exceeded permissible anchor loads. The described method is implemented in the in-house ship design environment E4, which already contains a method for manoeuvring simulations. The equations of motion are solved for three degrees of freedom: surge, sway and yaw. Any effects due to dynamic heel are considered quasi-statically. The method is based on a force model with components for environmental and body forces as well as propeller, rudder and steering forces for dynamic positioning applications. For the purpose of mooring system analysis an additional force component for the mooring line loads is introduced by using load-deflection curves. These curves can be calculated within E4 or imported from other sources. The resulting method allows detailed response calculations in the time-domain and can be used in various applications due to its great computational efficiency. In the presented paper the method is used for the analysis of a marine casualty due to harsh weather conditions.